Initial Experience with Technetium-99m HM-PAO Brain SPECT - Podreka, I; Suess, E; Goldenberg, G; Steiner, M; Brucke, T; Muller, Ch; Lang, W; Neirinckx, R.D; Deecke, L (The Journal of nuclear medicine (1978), 1987)
Technetium-99m hexamethylpropyleneamineoxime ([99mTc]HM-PAO) brain single photon emission computed tomography (SPECT) was performed with a dual head rotating scintillation camera. Normal tracer distribution and side/side differences of counting rates were obtained in 11 healthy volunteers. Almost stable gray/white matter ratios were found (1.97-2.1) in one normal subject during 2 hr after tracer administration. Eighty-three investigated patients had the following diagnoses (in parentheses is percent of positive findings in each group): cerebral vascular disease 18 (94.4%), epilepsy 23 (82.6%), extrapyramidal disorders 8 (100%), dementia 12 (100%), headache 11 (63.6%), psychiatric disorders 11 (27.3%). In addition, SPECT was performed in 28 male volunteers during motor or visual imagery tasks and a significant increase (p = 0.035) of relative tracer deposition was observed in the left inferior occipital region during visual imagery when compared with motor imagery. The results indicate that [99mTc]HM-PAO SPECT is valuable for demonstrating pathologic and physiologic changes of the brain.